4-Anilidopiperidine Derivatives for in vivo Imaging of μ-Opioid Receptors - Marton, János; Sipos, Attila; Berényi, Sándor; Glaenzel, Brita; Henriksen, Gjermund (Letters in Organic Chemistry, 2020)
A method for gram scale preparation of 2-fluoropropionyl-carfentanil was established, starting from 4-phenylamino-1-benzyl-4-piperidinecarboxylic acid. 2-Fluoropropionyl-carfentanil carboxylic acid and 2-chloropropionyl-carfentanil as precursors were synthesized for the radiosynthesis of 11C and/or 18F labelled 2-fluoropropionyl-carfentanil derivatives via two separate reaction routes. Conformational analysis of 2-fluoropropionyl-carfentanil was performed using computational methods. Calculated 1H and 13C-NMR shifts are presented.
Keywords: 4-anilidopiperidines